A de Novo ZMIZ1 Pathogenic Variant for Neurodevelopmental Disorder With Dysmorphic Facies and Distal Skeletal Anomalies - Lu, Guanting; Ma, Liya; Xu, Pei; Xian, Binqiang; Wu, Lianying; Ding, Jianying; He, Xiaoyan; Xia, Huiyun; Ding, Wuwu; Yang, Zhirong; Peng, Qiongling (Frontiers in Genetics, 2022)
Background: Neurodevelopmental disorder with dysmorphic facies and distal skeletal anomalies (NEDDFSA) is a rare syndromic disorder characterized by global neurodevelopmental delay, early-onset hypotonia, poor overall growth, poor speech/language ability, and additional common phenotypes such as eye anomalies, joint hypermobility, and skeletal anomalies of the hands and feet. NEDDFSA is caused by heterozygous pathogenic variants in the ZMIZ1 gene on chromosome 10q22.3 with autosomal dominant (AD) mode of inheritance. All the 32 reported cases with variants in ZMIZ1 gene had a genetic background in Caucasian, Hispanic, North African, and Southeastern Asian. Until now, there are no reports of Chinese patients with ZMIZ1 pathogenic variants. Methods: A 5-year-old girl was found to have the characteristic phenotypes of NEDDFSA. Array-Comparative Genomic Hybridization (array-CGH) and whole exome sequencing (WES) were applied for the trio of this female patient. Sanger sequencing was used to verify the selected variants. A comprehensive molecular analysis was carried out by protein structure prediction, evolutionary conservation, motif scanning, tissue-specific expression, and protein interaction network to elucidate pathogenicity of the identified ZMIZ1 variants. Results: The karyotype was 46, XX with no micro-chromosomal abnormalities identified by array-CGH. There were 20 variants detected in the female patient by WES. A de novo heterozygous missense variant (c.2330G > A, p.Gly777Glu, G777E) was identified in the exon 20 of ZMIZ1. No variants of ZMIZ1 were identified in the non-consanguineous parents and her healthy elder sister. It was predicted that G777E was pathogenic and detrimental to the spatial conformation of the MIZ/SP-RING zinc finger domain of ZMIZ1. Conclusion: Thus far, only four scientific articles reported deleterious variants in ZMIZ1 and most of the cases were from Western countries. This is the first report about a Chinese patient with ZMIZ1 variant. It will broaden the current knowledge of ZMIZ1 variants and variable clinical presentations for clinicians and genetic counselors.